An Account of Acute Adverse Drug Reactions Occurring in a Day-Care Chemotherapy Unit of a Tertiary Care Cancer Hospital—A Prospective Observational Study - Gonepalli Pravanika Sekhar; Krishna Mohan Mallavarapu; Senthil Rajappa; Santa Ayyagari; Pavan Kumar Boyela; Rakesh Pinninti; Narander Cheraku (Indian Journal of Medical and Paediatric Oncology)
Introduction Acute adverse drug reactions (ADRs) in day-care chemotherapy are not uncommon and are easily manageable on most occasions. However, sometimes they may lead to untoward events. It is paramount to document and analyze such events in contemporary medical oncology practice for the best utilization and planning of available personnel and resources.